Sistem Kontrol Otomatis dan Efesiensi Energi Listrik dari Penggunaan Air Cooler Berbasis IOT - Kemas Muhammad Caesar Jayadi; Muhamad Ariandi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Air Coolers are the right choice as an air conditioning tool compared to AC because they are much more energy efficient and environmentally friendly. In this system, the Air Cooler on/off function will be controlled automatically based on the room temperature detected by the DHT22 sensor. If the room temperature reaches 24o Celsius, the Air Cooler will be off. Then this automatic system is also able to control the on/off of the Air Cooler based on the number of people entering and leaving the room using the IR Proximity sensor. The Blynk application connected to a smartphone allows for regular monitoring of the voltage and current used by the Air Cooler. Then a comparison of the electrical energy used by the Air Cooler is carried out before and after using the system that has been designed. The conclusion obtained is that the system designed is able to control automatically and save electrical energy from using the Air Cooler.